Linearly polarized millimeter wave reflectarray with mutual coupling optimization - Shamsan, Zaid Ahmed; Abbasi, Muhammad Inam; Dahri, Muhammad Hashim; Kamarudin, Muhammad Ramlee; Ashyap, Adel Yahya Isa; Jamaluddin, Mohd Haizal; Sulaiman, Noor Hafizah; Khan, Muhammad Abbas; AlMuhanna, Khalid; Alorifi, Fawzi (Tech Science Press, 2022)
This work provides the design and analysis of a single layer, linearly polarized millimeter wave reflectarray antenna with mutual coupling optimization. Detailed analysis was carried out at 26 GHz design frequency usingthe simulations of the reflectarray unit cells as well as the periodic reflectarray antenna. The simulated results were verified by the scattering parameter and far-field measurements of the unit cell and periodic arrays, respectively. A close agreement between the simulated and measured results was observed in all the cases. Apart from the unit cells and reflectarray, the waveguide and horn antenna were also fabricated to be used in the measurements. The measured scattering parameter results of the proposed circular ring unit cells provided a maximum reflection loss of 2.8 dB with phase errors below 10°. On the other hand, the measured far-field results of the 20 × 20 reflectarray antenna provided a maximum gain of 26.45 dB with a maximum 3 dB beam width of 12° and 1 dB gain drop bandwidth of 13.1%. The performance demonstrated by the proposed reflectarray antenna makes it a potential candidate to be used in modern-day applications such as 5th Generation (5G) and 6th Generation (6G) communication systems.